IMPLEMENTATION OF QUANTUM TEACHING MODELS IN LISTENING THE SHORT STORIES IN SMA 2 RAMBAH HILIR (PENERAPAN MODEL QUANTUM TEACHING DALAM MENYIMAK CERITA PENDEK DI SMA NEGERI 2 RAMBAH HILIR) - Arianti, Rita; Herwandi, Herwandi (Universitas PGRI Sumatera Barat, 2018)
This research is motivated by the low level of studentsskills in listening to short stories.This can be seen in the value of listening to students who are under the minimumcompleteness criteria (75).This is due to the lack of interest and motivation of studentsin listening to short stories, learning models applied by teachers that are less precise,and the classroom atmosphere that is less supportive of the achievement of listening learning objectives. This type of research is Classroom Action Research. This researchmethod is qualitative and quantitative methods. The purpose of this study was toincrease the activity and student learning outcomes in learning to listen to short storiesby applying theQuantum Teaching model in class XI IPS 1 of SMA Negeri 2 Rambah.The results of this study were (1) improving the quality of student activity from cycle I by46%, cycle II by 62%, cycle III by 76%, and cycle IV by 96%, there was an increase instudent activity in listening to short stories to be very high quality, and (2) thecompleteness of learning outcomes from the first cycle is 41.38% with an average valueof 73.06, the second cycle is 55.17% with an average value of 78.65, the third cycle is72, 41%with an average value average of 82.07, and cycle IV of 100% with an averagevalue of 87.10. Based on the results of the study it can be concluded that the applicationof the Quantum Teaching model in learning to listen to short stories can increase theactivity and learning outcomes of class XI IPS 1 SMA Negeri 2 Rambah Hilir.